(1+cotx+tanx)(sinx-cosx)bysec^3x-cosec^3x=sin^2xcos^2x
Answers
Answered by
18
=(sinx.cosx + 1)/(1+cosx.sinx)×(sinx.cosx)
=sinx.cosx
=R.H.S
Hence,Proved.
I have used the identity.
Attachments:
![](https://hi-static.z-dn.net/files/d59/9d6513db54ce79535f15ebc8832a0188.jpg)
Answered by
5
(1+cotx+tanx)(sinx-cosx)bysec^3x-cosec^3x=sin^2xcos^2x
Proved below.
Step-by-step explanation:
Given:
L.H.S=
We know that,
;
;
;
=
=[/tex]
=
We know that
Also
=
=
=sin^2xcos^2x
=R.H.S.
Hence proved.
Similar questions